If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 + -1c = 26 Solving 44 + -1c = 26 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-44' to each side of the equation. 44 + -44 + -1c = 26 + -44 Combine like terms: 44 + -44 = 0 0 + -1c = 26 + -44 -1c = 26 + -44 Combine like terms: 26 + -44 = -18 -1c = -18 Divide each side by '-1'. c = 18 Simplifying c = 18
| 26+c=19 | | -8=-17+x-14 | | 4(x-1)=2(x+4) | | a+7=-3 | | 2a+1a=24 | | 5c+6=(3+2c) | | x+19=32 | | z=10+3(x+y) | | 4x-6=3x+2 | | 3(n-1)=1.5(n+2) | | 63=9(2y-3) | | 4(2p-1)=28 | | 2(3+x)=14 | | 8(z+2)-5(z+3)=16 | | -16+x=x-16 | | 4z=7z+12 | | 2(3x-3)+5(x-4)=4(x+2) | | 4(x-3)=2(x-1) | | 23-12x=-(7+2x) | | -1+10=5b-8-4b | | x-4x=-5x-20 | | 56x^2+8x=0 | | 2a^2-9a+3=0 | | 10x^2-26x+12=0 | | 4x^2+8x-77=0 | | 3v^2+28v+49=0 | | x^2=5x+2 | | -3(5t-12)=4t-21 | | 2k^2+3k-14=0 | | 3g^2-7g+2=0 | | 42=6v | | x^2+15x+49=0 |